Scrabble game technique: A game changer for English vocabulary learning - Sari, Diana Fauzia; Sahardin, Rosnani; Yani, Vida; Yusuf, Yunisrina Qismullah (Englisia: Journal of Language, Education, and Humanities, 2022)
Students’ learning outcomes of vocabulary mastery in reading comprehension at junior high schools in Banda Aceh, Indonesia, are relatively low. To tackle the issue, the Scrabble Game Technique (hereafter, SGT) is hoped to be a game-changer. This study aims to investigate EFL students’ learning outcomes through the use of the SGT in learning English vocabulary through narrative texts to seventh-grade students at a junior high school. The aspects assessed for each type of vocabulary included nouns, verbs, pronouns, adverbs, adjectives, and conjunctions. The research design was quantitative with pre-experimental research that used a one-group pre-test post-test design to measure the students’ learning outcomes after three treatments with the SGT. A total of 30 seventh-grade students were selected by purposive sampling. The instrument used to collect data was a test, comprising 30 questions in total, with 18 multiple choices, 6 fill-in-the-blanks, and 6 matching-the-word. The tests were further analyzed using the right-hand t-test after the pre-requisite test was met. It was found that the percentage of mastery of nouns and verbs in the post-test was better than the pre-test, with the improvement of nouns at 93%, verbs at 91%, pronouns at 84%, adverbs at 72%, adjectives at 71%, and conjunctions at 71%. Furthermore, the t-count was 19.68 with p = 0.05, dk = 29, and t-table = 1.70. It was concluded that students’ learning outcomes were better after being taught through the SGT.